2019
DOI: 10.1016/j.crfs.2019.07.001
|View full text |Cite
|
Sign up to set email alerts
|

UHPLC-ToF-MS method for determination of multi-mycotoxins in maize: Development and validation

Abstract: An Ultra-High Performance Liquid Chromatography combined with Time-of-Flight Mass Spectrometry (UHPLC–ToF-MS) method has been developed for determination of nine mycotoxins, namely aflatoxins (AFB 1 , AFB 2 , AFG 1 and AFG 2 ), ochratoxin A (OTA), zearalenone (ZEA), toxin T2 (T2) and fumonisins (FB 1 and FB 2 ) in maize. The method included a two-step extraction with acetoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…The analytical procedure used to quantify the mycotoxins content of maize grains is described by Silva et al [ 36 ]. Briefly, two grams of maize flour were weighted, 100 μL internal standard ZAN (10 μg/mL) was added, and samples extracted with 10 mL of acetonitrile 80% ( v / v ) for 1 h in an orbital shaker at 110 rpm (Kotterman 4010, Uetze/Hanigsen, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analytical procedure used to quantify the mycotoxins content of maize grains is described by Silva et al [ 36 ]. Briefly, two grams of maize flour were weighted, 100 μL internal standard ZAN (10 μg/mL) was added, and samples extracted with 10 mL of acetonitrile 80% ( v / v ) for 1 h in an orbital shaker at 110 rpm (Kotterman 4010, Uetze/Hanigsen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Have been reported in Spain [ 25 ], South Korea [ 26 ], Republic of Serbia [ 27 ], Slovenia [ 7 ], Croatia [ 28 ], Egypt [ 29 ], Ethiopia [ 30 ], China [ 31 ], India [ 32 ], and Brazil [ 33 ], and two studies have reported the incidence of mycotoxins during storage [ 34 , 35 ]. In Portugal, few studies have mentioned the fungal species prevalence and mycotoxins occurrence in maize grains after harvest [ 36 , 37 ] and no studies have reported their accumulation during storage. Thus, due to the high toxicity of these mycotoxins and the influence of environmental conditions, the objective of this study was to investigate the occurrence of Fusarium species and consequent contamination of related mycotoxins in Portuguese maize grains stored for six months in barrels, monitoring CO 2 , temperature, and relative humidity parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Literature data concerning mycotoxins stability in organic solvents and extracts are scattered and devoted to a single or several selected representatives of mycotoxins. The current trend towards the development of multi-analyte methods, however, demands the confirmation of standard solutions stability for dozens of analytes: the whole spectrum of regulated mycotoxins [5,6] or a broad range of fungal metabolites [7][8][9]. Common factors affecting the stability of standard solution are the solvents ability to degrade analyte and to get evaporated, temperature and UV-irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid Chromatography has a range of analytical characteristics that can be utilized for mycotoxin analysis. In combination with other analytical instruments, such as mass spectrometry or gas chromatography, it can yield results that demonstrate different stereoisomer of AF or FM [24]. HPLC can present a procedure with high selectivity, and simultaneous quantification of mycotoxin [19,24,25].…”
Section: Liquid Chromatographymentioning
confidence: 99%
“…In combination with other analytical instruments, such as mass spectrometry or gas chromatography, it can yield results that demonstrate different stereoisomer of AF or FM [24]. HPLC can present a procedure with high selectivity, and simultaneous quantification of mycotoxin [19,24,25]. Nonetheless, spectral libraries are needed, meticulous sample preparation is required, and major costs are associated with the chemical and personnel required to operate through this method.…”
Section: Liquid Chromatographymentioning
confidence: 99%